Górnictwo węgla brunatnego w dawnym powiecie sulechowsko-świebodzińskim, część I: rejon Lubrza - Świebodzin = Lignite mining in the Sulechów-Świebodzin county, part I: Lubrza - Świebodzin area - Gontaszewska-Piekarz, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work contains available information on historical lignite mines in the former (pre-war) Świebodzińsko-Sulechowski county. This part of the article includes the area between Lubrza and Świebodzin, where lignite was discovered as early as 1824.
Keywords: Świebodzin (okręg); górnictwo węgla brunatnego; historia górnictwa; lignite mining; history of mining